2013
DOI: 10.1002/hep.26429
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic macrophages but not dendritic cells contribute to liver fibrosis by promoting the survival of activated hepatic stellate cells in mice

Abstract: Although it is well established that hepatic macrophages play a crucial role in the development of liver fibrosis, the underlying mechanisms remain largely elusive. Moreover, it is not known whether other mononuclear phagocytes such as dendritic cells contribute to hepatic stellate cell (HSC) activation and liver fibrosis. Here we show for the first time that hepatic macrophages enhance myofibroblast survival in an NF-κB-dependent manner, and thereby promote liver fibrosis. Microarray and pathway analysis reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
412
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 495 publications
(455 citation statements)
references
References 46 publications
16
412
0
3
Order By: Relevance
“…Therefore, copious amount of macrophages would be recruited from bone marrow (BM), aggregate in inflammatory sites, and play a crucial role in inflammation and fibrosis (16). Indeed, it has been reported that the inflammation and fibrosis of injured liver were ameliorated after the depletion of macrophages (19). We have also found that reducing the recruitment of BM-derived monocytes/macrophages (BMM) can attenuate hepatic inflammation and fibrosis (20).…”
mentioning
confidence: 65%
See 2 more Smart Citations
“…Therefore, copious amount of macrophages would be recruited from bone marrow (BM), aggregate in inflammatory sites, and play a crucial role in inflammation and fibrosis (16). Indeed, it has been reported that the inflammation and fibrosis of injured liver were ameliorated after the depletion of macrophages (19). We have also found that reducing the recruitment of BM-derived monocytes/macrophages (BMM) can attenuate hepatic inflammation and fibrosis (20).…”
mentioning
confidence: 65%
“…The levels of ALT and AST were downregulated, indicating the blockade of CB1-protected hepatocytes from damage. Additionally, fibrosis was markedly attenuated, possibly due to the fact that blockade of CB1 reduced the levels of profibrogenic cytokines and growth factors such as TNF-a, IL-6, and TGF-b1, which can drive hepatic stellate cell activation or promote the survival of activated hepatic stellate cells (19,41). However, other studies have also shown that macrophages revealed distinct roles during liver injury (42) and their depletion exacerbated liver injury (43).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Next to their fundamental role in the recognition and clearance of invading pathogens [4][5][6] , macrophages have increasingly come into focus in atherosclerosis, fibrosis, obesity, and cancer [7][8][9][10] . A reproducible method for the generation of human macrophages is therefore crucial for an understanding of these pathologies.…”
Section: Introductionmentioning
confidence: 99%
“…such as viral hepatitis and alcohol consumption, KCs can be induced into an activated state in which they secrete a wide variety of proinflammatory cytokines, such as IL-6, IL-10, IL-13, TNF-α, and TGF-β, further activating HSCs. Macrophages can play an indirect role in the development of liver fibrosis (37)(38)(39)(40) (41). However, the correlation between LSECs and macrophages in chronic liver diseases and the mechanism of their interaction remains unclear and needs to be examined further.…”
Section: Structural Changes and Triggers Of Defenestrationmentioning
confidence: 99%